Time-varying motor control strategy for proximal-to-distal sequential energy distribution: insights from baseball pitching - Kozo, N. (Journal of Experimental Biology, 2021)
The importance of a proximal-to-distal (P-D) sequential motion in baseball pitching is generally accepted; however, the mechanisms behind this sequential motion and motor control theories that explain which factor transfers mechanical energy between the trunk and arm segments are not completely understood. This study aimed to identify the energy distribution mechanisms among the segments and determine the effect of the P-D sequence on the mechanical efficiency of the throwing movement, focusing on the time-varying motor control. The throwing motions of 16 male collegiate baseball pitchers were measured by a motion capture system. An induced power analysis was used to decompose the system mechanical energy into its muscular and interactive torque-dependent components. The results showed that the P-D sequential energy flow during the movement was mainly attributed to three different joint controls of the energy generation and muscular torque- and centrifugal force-induced energy transfer. The trunk muscular torques provided the primary energy sources of the system mechanical energy, and the shoulder and elbow joints played the roles of the energy-transfer effect. The mechanical energy expenditure on the throwing hand and ball accounted for 72.7% of the total muscle work generated by the trunk and arm joints (329.2 J). In conclusion, the P-D sequence of the throwing motion is an effective way to utilize the proximal joints as the energy source and reduce muscular work production of the distal joints. This movement control assists in efficient throwing, and is consistent with the theory of the leading joint hypothesis.